Influential Article Review - Globalization of Highly Digitized Companies - Strickland, Marian; Wise, Tara; Bishop, Pat (Journal of Strategic Innovation and Sustainability, 2019)
This paper examines technology. We present insights from a highly influential paper. Here are the highlights from this paper: Highly digitized organizations can potentially grow faster internationally, relatively to more traditional organizations. They can do so by providing a platform, and by fostering an ecosystem of complementary third party developers, some of which are foreign. This paper proposes a theoretical link between International Business theory and the literature related to the platform-ecosystem organizational form. It emphasizes implications for psychic distance, liability of foreignness, and speed and pattern of internationalization. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.